ANALISIS CITRA PEREMPUAN PADA NOVEL 172 DAYS KARYA NADZIRA SHAFA DAN RELEVANSINYA SEBAGAI E MODUL PEMBELAJARAN NOVEL KELAS XII (KAJIAN KRITIK SASTRA FEMINIS) - MARIYAM, SITI; SYAFRONI, RONI NUGRAHA; MELIASANTI, FERINA (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
The purpose of this study is to 1) Describe the intrinsic elements of the novel 172 Days by Nadzira Shafa 2) Describe the image of women in the novel 172 Days by Nadzira Shafa, and 3) Describe the results of the research on the novel 172 Days as an E Module for learning novels for class XII. This study is a qualitative descriptive study. The techniques used are literature study techniques, observation, and notes. Data analysis is carried out through data collection, data reduction, data presentation, and drawing conclusions. The results of the study show 1) Major theme: the struggle of a woman. Minor themes consist of themes of depression, happiness, sadness, and the struggle of a woman. 2) Results of the image of women: physical aspects, namely graceful, beautiful, pregnant, weak pregnancy, miscarriage, young women. Psychological aspects: depression, women's independence in thinking, steadfast in facing the death of a husband, women who are full of consideration, wise adult women, women who are able to be grateful, women's self-confidence, restless, anxious, sincere, and independent. Social aspects of the family: good wife, respecting husband, responsibility towards husband, loving husband, daughter-in-law, daughter who is devoted to parents, strong wife. Social aspects of society: educated women, female students, helping each other between friends, women socializing in scientific assemblies, and Arab descent. The results of this study are relevant as teaching materials for E-Module novel learning for class XII. ABSTRAKTujuan penelitian ini yaitu untuk 1) Mendeskripsikan unsur intrinsik novel 172 Days karya Nadzira Shafa 2) Mendeskripsikan citra perempuan pada novel 172 Days karya Nadzira Shafa, dan 3) Mendeskripsikan hasil penelitian novel 172 Days sebagai E Modul pembelajaran novel kelas XII. Penelitian ini merupakan penelitian deskriptif kualitatif. Teknik yang digunakan yaitu teknik studi pustaka, simak, dan catat. Análisis data yang dilakukan melalui pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil Penelitian menunjukan 1) Tema mayor: perjuangan seorang perempuan. Tema minor terdiri dari tema keterpurukan, kebahagiaan, kesedihan, dan perjuangan seorang perempuan. 2) Hasil citra perempuan: aspek fisik yaitu sosok anggun, cantik, hamil, kandungan lemah, keguguran, perempuan muda. Aspek psikis: depresi, kemandirian perempuan dalam berfikir, tabah dalam menghadapi kematian suami, perempuan yang penuh pertimbangan, perempuan dewasa yang bijak, perempuan yang mampu bersyukur, keyakinan diri perempuan, gelisah, cemas, ikhlas, dan mandiri. Aspek sosial keluarga: istri yang baik, menghormati suami, tanggung jawab terhadap suami, mencintai suami, menantu, anak perempuan yang berbakti kepada orang tua, istri yang kuat. Aspek sosial masyarakat: perempuan berpendidikan, mahasiswi, saling membantu antar teman, perempuan bersosialisasi majelis ilmu, dan keturunan arab. Hasil penelitian ini di relevansikan sebagai bahan ajar E-Modul pembelajaran novel kelas XII.